Seasonal and Mesoscale Variability of the Two Atlantic Water Recirculation Pathways in Fram Strait - Hofmann, Zerlina; von Appen, Wilken‐Jon; Wekerle, Claudia; von Appen, Wilken‐Jon; 1 Physical Oceanography of the Polar Seas Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Wekerle, Claudia; 1 Physical Oceanography of the Polar Seas Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany (Journal of Geophysical Research: Oceans, 2021)
Atlantic Water (AW), which is transported northward by the West Spitsbergen Current (WSC), partly recirculates (i.e., turns westward) in Fram Strait. This determines how much heat and salt reaches the Arctic Ocean, and how much joins the East Greenland Current on its southward path. We describe the AW recirculation's location, seasonality, and mesoscale variability by analyzing the first observations from moored instruments at five latitudes in central Fram Strait, spanning a period from August 2016 to July 2018. We observe recirculation on the prime meridian at 78°50’N and 80°10’N, respectively south and north of the Molloy Hole, and no recirculation further south at 78°10’N and further north at 80°50’N. At a fifth mooring location northwest of the Molloy Hole at 79°30’N, we observe some influence of the two recirculation pathways. The southern recirculation is observed as a continuous westward flow that carries AW throughout the year, though it may be subject to broadening and narrowing. It is affected by eddies in spring, likely due to the seasonality of mesoscale instability in the WSC. The northern recirculation is observed solely as passing eddies on the prime meridian, which are strongest during late autumn and winter, and absent during summer. This seasonality is likely affected both by the conditions set by the WSC and by the sea ice. Open ocean eddies originating from the WSC interact with the sea ice edge when they subduct below the fresher, colder water. Plain Language Summary: West of Spitsbergen, the so‐called West Spitsbergen Current (WSC) carries relatively warm water towards the Arctic Ocean. Part of this water turns westward before it reaches the Arctic Ocean. Another current transports it back south along the Greenland shelf. We look at observations of temperature, salinity, and flow velocity from two years in the region. We find that the warm water flows westwards at two latitudes. At 78°50’N it flows westwards throughout the year, but is affected by eddies in the ocean during spring. These ...